Large scale use of SARS-CoV-2 antigen-based detection tests: a three-month experience in Guatemala, June-August 2020 - Lorena Gobern; Liz Parra; Antonio A. Paredes; Rafael A. León; Jairo Mendez-Rico; Marc Rondy (Pan American Health Organization, 2023)
Objectives. To measure protocol adherence and antigen-based detection tests (AgDT) negative predictive value after 3 months of massive use as a diagnostic tool for COVID-19 in Guatemala. Methods. The study period included nasopharyngeal swabs taken between March 12 and August 31, 2020, which results were entered in the national COVID-19 information system. Proportional increase in testing between one month before and one month after the introduction of AgDT (May 9-June 8 vs. June 9-July 8) was measured. Results. After AgDT introduction, there was a 139% increase in SARS-CoV-2 testing. Between June 9 and August 31, 7.8% of 110 657 AgDT-negative patients had follow-up RT-PCR testing. Of them, 30% were RT-PCR positive. Conclusions. While introducing AgDT improved access to diagnostics, ensuring the availability of timely RT-PCR capacities to confirm diagnosis is also key.